The molecular structure and biological functions of RNA methylation, with special emphasis on the roles of RNA methylation in autoimmune diseases. (3rd April 2022) - Zhou, Wanwan; Wang, Xiao; Chang, Jun; Cheng, Chenglong; Miao, Chenggui
Abstract: Autoimmune diseases such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and systemic vasculitis are caused by the body's immune response to autoantigens. The pathogenesis of autoimmune diseases is complex. RNA methylation is known to play a key role in disease progression as it regulates almost all aspects of RNA processing, including RNA nuclear export, translation, splicing, and noncoding RNA processing. This review summarizes the mechanisms, molecular structures of RNA methylations and their roles in biological functions. Similar to the roles of RNA methylation in cancers, RNA methylation in RA and SLE involves "writers" that deposit methyl groups to form N6-methyladenosine (m6A) and 5-methylcytosine (m5C), "erasers" that remove these modifications, and "readers" that further affect mRNA splicing, export, translation, and degradation. Recent advances in detection methods have identified N1-methyladenosine (m1A), N6, 2-O-dimethyladenosine (m6Am), and 7-methylguanosine (m7G) RNA modifications, and their roles in RA and SLE need to be further studied. The relationship between RNA methylation and other autoimmune diseases has not been reported, and the roles and mechanisms of RNA modifications in these diseases need to be explored in the future.